Theory and Applications of Ordered Fuzzy Numbers: A Tribute to Professor Witold Kosiński - Prokopowicz, Piotr; Czerniak, Jacek; Mikołajewski, Dariusz; Apiecionek, Łukasz; Ślȩzak, Dominik (Studies in Fuzziness and Soft Computing, 2017)
fuzzy arithmetic; defuzzyfication; fuzzy prediction models; analysis; trend processing; uncertainty modeling; propagation of uncertainty; Kosinski's fuzzy numbers